The Effects Intradialytic Exercise On Hemodialysis: a systematic review - Fadlilah, Lia; Ratri, Tifany Hayuning; Yuliani, Feri Catur (Jurnal Ners, 2025)
Hemodialysis is the most common method used to treat chronic kidney disease (CKD). However, it is still accompanied by increasing morbidity and mortality, with cardiovascular disorders as the main cause of death. Hemodialysis can lead to decreased capacity and functional muscle mass, inflammation, endothelial dysfunction, and bone mineral disease (cardiovascular disorders). Exercise or activity programs during hemodialysis (intradialytic) come in many forms, all aimed at improving muscle mass, bone strength, cardiorespiratory health, physical fitness, and enhancing the quality of life. This study will systematically review previous journals discussing the impact of training or physical activity on chronic kidney disease patients undergoing hemodialysis, regarding all factors that can improve the quality of life for CKD patients undergoing HD. The literature search process was conducted on research from the last 5 years (2016-2020) in English selected from several indexed electronic databases (Scopus, Science Direct, CINAHL, Pubmed, Oxford, SAGE). A search using a search engine yielded a total of 301 articles, and after screening, 13 were selected based on criteria and were of RCT research design. The results of the studies show that the appropriate and safe selection of intradialytic exercise for patients, without requiring extra time, can improve physical activity and sleep quality, leg muscle mass, stimulate bone alkaline phosphatase which can prevent osteoporosis, lower blood pressure, improve respiratory function and functional capacity, enhance physical function, reduce inflammation, improve nutrition, increase bone mineral density, improve exercise tolerance, increase Kt/V, enhance serum creatinine clearance, blood urea, and serum potassium phosphate. The positive impact of exercise during hemodialysis will result in an improved quality of life, and a decrease in morbidity and mortality in CKD patients undergoing hemodialysis. Keywords: exercise; hemodialysis; Intradialytic